Anti-Americanism in Lebanon: an empirical assessment - Haddad, Simon (Islam and Christian-Muslim relations, 2004)
This paper aims at empirically assessing Lebanese reactions to retaliation attacks against US targets. The author proposes that receptiveness to tenets of religious fundamentalism influences approval of these attacks. In view of the surge of Islamic militancy in recent years, he further proposes that Muslim respondents would be likely to show greater support for the attacks than Christians. The data come from a quota sample, consisting of 607 Christian and Muslim respondents of both genders, conducted in the Greater Beirut area during the months of November and December 2002. The findings support the proposition that proneness to religious fundamentalism is related to approval of the attacks, but they also demonstrate the insignificance of religious fundamentalism in explaining Christian support for retaliation attacks.